EFFECT OF ORGANIZATIONAL BEHAVIOUR ON CORPORATE EFFECTIVENESS - Panja, Anup Kumar (The journal of contemporary issues in business and government, 2021)
The design of work as well as the psychological, emotional, and interpersonal behavioral dynamics that influence organizational success are all covered under organizational behavior. Management is critical in organizational behavior since it is focused with the study of overseeing operations and monitoring people to fulfill certain duties regarding the efficiency of the company. Management places a premium on the planning, implementation, and coordination of various projects. For business effectiveness, administrative and organizational structures are necessary. While individuals and groups have their own unique perspectives, incorporating skills, knowledge, beliefs, goals, and attitudes into the organization, and so influencing it modifies or restructures individuals and groups by its structure, culture, policies, and politics, on the other hand, power, processes, and the roles that employees in the organization are supposed to play. There were 125 participants in this exploratory research project, and the results revealed a strong positive link between the variables of interest. Because of time constraints and a lack of current relevant literature, the study was never comprehensive; consequently, more research could be done to evaluate the association between personality characteristics and performance in the public sector, which is less productive than the private sector. Organizations should provide emotional intelligence programmes for their members as a key pattern for boosting cooperative behavior and corporate effectiveness, according to the findings of this inquiry.